Mutations in DNA-Binding Loop of NFAT5 Transcription Factor Produce Unique Outcomes on Protein–DNA Binding and Dynamics - Li, Minghui; Shoemaker, Benjamin A; Thangudu, Ratna R; Ferraris, Joan D; Burg, Maurice B; Panchenko, Anna R (The journal of physical chemistry. B, 2013)
The nuclear factor of activated T cells 5 (NFAT5 or TonEBP) is a Rel family transcriptional activator and is activated by hypertonic conditions. Several studies point to a possible connection between nuclear translocation and DNA binding; however, the mechanism of NFAT5 nuclear translocation and the effect of DNA binding on retaining NFAT5 in the nucleus are largely unknown. Recent experiments showed that different mutations introduced in the DNA-binding loop and dimerization interface were important for DNA binding and some of them decreased the nuclear–cytoplasm ratio of NFAT5. To understand the mechanisms of these mutations, we model their effect on protein dynamics and DNA binding. We show that the NFAT5 complex without DNA is much more flexible than the complex with DNA. Moreover, DNA binding considerably stabilizes the overall dimeric complex and the NFAT5 dimer is only marginally stable in the absence of DNA. Two sets of NFAT5 mutations from the same DNA-binding loop are found to have different mechanisms of specific and nonspecific binding to DNA. The R217A/E223A/R226A (R293A/E299A/R302A using isoform c numbering) mutant is characterized by significantly compromised binding to DNA and higher complex flexibility. On the contrary, the T222D (T298D in isoform c) mutation, a potential phosphomimetic mutation, makes the overall complex more rigid and does not significantly affect the DNA binding. Therefore, the reduced nuclear–cytoplasm ratio of NFAT5 can be attributed to reduced binding to DNA for the triple mutant, while the T222D mutant suggests an additional mechanism at work.